URGENSI REGULASI TELEMEDICINE PASCA PANDEMI COVID-19 DI INDONESIA - Ruli Purwanto (Bajang Institute, 2025)
This study examines the urgency of telemedicine regulation in Indonesia after the COVID-19 pandemic against the backdrop of the rapid development of digital-based health services that have not been balanced by a comprehensive legal umbrella. Legal uncertainty, weak patient data protection, and the absence of a clear accountability mechanism are the main problems faced. This study uses a normative legal method with a statutory and conceptual regulatory approach, to analyze legal norms relevant to telemedicine practices. The results of the study show that the current regulations are partial and temporary, so that an ideal regulatory construction is needed that includes aspects of formal legal recognition, personal data protection, standardization of medical personnel competencies, and a legal accountability system. Thus, telemedicine in the future can function as a permanent part of a health service system that is equitable and based on patient rights